Starting Off On the Right Foot: Differential Diagnosis of Metatarsalgia - Hicks , B.; Neeley , S.; Kuhn , K.; Bartret , A.; Stevens , K.; , (Seram, 2021)
Background Information: Forefoot pain, or metatarsalgia, is a common clinical problem. Numerous disease processes can produce pain in the region of the metatarsal bones, and the diagnosis may be difficult to establish based on clinical findings alone. These disease processes include traumatic injuries of the soft tissues and bones, Freiberg’s infraction, infection, arthritis, tendon disorders and soft tissue masses. The accurate diagnosis of these pathologies is heavily dependent on imaging, particularly Magnetic Resonance Imaging (MRI). The purpose of this educational exhibit is to explore the different pathologies resulting in metatarsalgia and describe specific imaging features of each condition. Educational Goals/Teaching Points: Discuss the common causes of metatarsalgia. Describe the imaging characteristics of the most common etiologies of metatarsalgia utilizing multiple modalities. Illustrate how MR imaging allows a specific diagnosis based on the location, signal intensity characteristics, and morphologic features of the abnormality. Briefly outline the appropriate management decisions for some of these conditions. Key Anatomic/Physiologic Issues and Imaging Findings/Techniques: We will review the pathology-specific anatomy of the forefoot and describe unique imaging characteristics of conditions resulting in metatarsalgia, including traumatic injuries to the 1st metatarsophalangeal-sesamoid complex (turf toe) and lesser plantar plate, sesamoiditis, stress or insufficiency fracture, Freiberg’s infraction, infection such as osteomyelitis and septic arthritis, arthropathies including osteoarthritis, crystal arthopathy, and calcium hydroxyapatite deposition; tendon disorders, non-neoplastic soft tissue masses such as intermetatarsal bursitis, Morton’s neuroma and plantar fibroma. Conclusion: This educational exhibit will provide a comprehensive overview of conditions resulting in metatarsalgia, with an emphasis on MRI, and will outline the management of disorders that can produce discomfort in this region.